ARGUMENTASI DALAM WACANA SURAT GUGAT CERAI DI PENGADILAN AGAMA KOTA PALANGKA RAYA (THE ARGUMENTATION ON DISCOURSE OF DIVORCE ACCUSATION PAPER IN RELIGIOUS COURT AT PALANGKA RAYA) - Vera Noviana (Universitas Lambung Mangkurat, 2018)
AbstractThe Argumentation on Discourse of Divorce Accusation Paper in Religious Court at PalangkaRaya. Divorce paper or divorce accusation paper contains arguments that serve as an excuse to convincethe head of Religious Court in applying for or suing a divorce. Therefore, this study examines (1) theform of argumentation structure, (2) the argumentation method, and (3) the argumentation content ondiscourse of divorce accusation paper based on gender perspective. This study uses descriptive qualitativeapproach. The data source of this study is taken from 16 pieces of divorce accusation papers which consistof 8 divorce papers and 8 divorce accusation papers which are collected since May till December 2016.The results obtained are as follows. First, the argumentation structures on discourse of divorce accusationpaper consist of (1) statement, (2) reason, (3) justification, (4) supporter, and (5) modal. Secondly, theargumentation method on discourse of divorce accusation paper consist of two main parts, namely (1)the argumentation composition/component and (2) topic development method. The argumentationcomposition paper consists of three main parts, namely (a) introduction, (b) argumentation body and(c) conclusion. While the component of divorce accusation paper also consists of three main parts; theyare (a) the identity of the parties, (b) posita and (c) petitum. Third, the argumentation content based ongender perspective contains about (1) functional structural gender concerning in position and role thatcontrary to the state, and (2) argumentation style.Key words: argumentation, divorce accusation paperAbstrakArgumentasi dalam Wacana Surat Gugat Cerai di Pengadilan Agama Kota Palangka Raya. Suratcerai talak maupun surat cerai gugat mengandung argumentasi yang dijadikan alasan untuk meyakinkanketua Pengadilan Agama dalam mengajukan permohonan atau gugatan perceraian. Oleh karena itu,penelitian ini mengkaji tentang (1) wujud struktur argumentasi, (2) metode argumentasi, dan (3) isiargumentasi wacana surat gugat cerai berdasarkan perspektif gender. Penelitian ini menggunakanpendekatan deskriptif kualitatif. Sumber data penelitian ini mengambil 16 buah surat gugat cerai yangterdiri dari 8 buah surat cerai talak dan 8 buah surat gugat cerai yang diambil dari bulan Mei sampai16bulan Desember 2016. Hasil penelitian yang diperoleh adalah sebagai berikut. Pertama, strukturargumentasi dalam wacana surat gugat cerai terdiri atas (1) pernyataan, (2) alasan, (3) pembenaran,(4) pendukung dan (5) modal. Kedua, metode argumentasi dalam wacana surat gugat cerai terdiriatas dua bagian utama, yaitu (1) komposisi/komponen argumentasi dan (2) metode pengembangantopik. Komposisi argumentasi surat terdiri dari tiga bagian utama, yaitu (a) pendahuluan, (b) tubuhargumentasi dan (c) kesimpulan. Sementara itu, komponen surat gugatan juga terdiri dari tiga bagianutama, yaitu (a) identitas para pihak, (b) posita dan (c) petitum. Ketiga, isi argumentasi berdasarkanperspektif gender berisi tentang (1) gender struktural fungsional mengenai kedudukan dan peran yangbertolak belakang dengan keadaan, dan (2) gaya argumentasi.Kata-kata kunci: argumentasi, surat gugat cerai